LEFT HAND THUMB IMPRINT PATTERNS AMONG MEDICAL STUDENTS - Khan, Omair; Haroon, Muhammad Zeeshan; Rashid, Muhammad Adnan; Khan, Muhammad Naseem; Khan, Delawar (Journal of Ayub Medical College Abbottabad, 2017)
Background: Finger printing is an absolute method of identification. Recovery of finger prints from a crime scene is an important method of Forensic identification. Human finger prints are detailed, unique, difficult to alter, easily classifiable and durable over life making them stable and long-term tool of human identification. Methods: This cross-sectional study was conducted on 95,3rd year MBBS students of Ayub Medical College Abbottabad from December 2014 to August 2015 to establish the frequency of left hand thumb imprints by rolling and plain method. Results: Study shows Loops among most common finger print pattern in 55 (58%) students out of 95, followed by whorls 33 (35%), arches 5 (5%) and composite 2 (2%). Conclusion: It is thus concluded that most common finger print pattern is loops followed by whorls, arches and composite. Keywords: Identity, Loops; Whorl, Arches; Composite